Maternal plasma levels of oxytocin during breastfeeding-A systematic review - Uvnäs-Moberg, Kerstin; Ekström-Bergström, Anette; Buckley, Sarah J.; Massarotti, Claudia; Pajalić, Zada; Luegmair, Karolina; Kotłowska, Alicia; Lengler, Luise; Olza, Ibone; Grylka-Baeschlin, Susanne; Leahy-Warren, Patricia; Hadjigeorgiou, Eleni; et al. (My University, 2020)
Introduction Oxytocin is a key hormone in breastfeeding. No recent review on plasma levels of oxytocin in response to breastfeeding is available. Materials and methods Systematic literature searches on breastfeeding induced oxytocin levels were conducted 2017 and 2019 in PubMed, Scopus, CINAHL, and PsycINFO. Data on oxytocin linked effects and effects of medical interventions were included if available. Results We found 29 articles that met the inclusion criteria. All studies had an exploratory design and included 601 women. Data were extracted from the articles and summarised in tables. Breastfeeding induced an immediate and short lasting (20 minutes) release of oxytocin. The release was pulsatile early postpartum (5 pulses/10 minutes) and coalesced into a more protracted rise as lactation proceeded. Oxytocin levels were higher in multiparous versus primiparous women. The number of oxytocin pulses during early breastfeeding was associated with greater milk yield and longer duration of lactation and was reduced by stress. Breastfeeding-induced oxytocin release was associated with elevated prolactin levels; lowered ACTH and cortisol (stress hormones) and somatostatin (a gastrointestinal hormone) levels; enhanced sociability; and reduced anxiety, suggesting that oxytocin induces physiological and psychological adaptations in the mother. Mechanical breast pumping, but not bottle-feeding was associated with oxytocin and prolactin release and decreased stress levels. Emergency caesarean section reduced oxytocin and prolactin release in response to breastfeeding and also maternal mental adaptations. Epidural analgesia reduced prolactin and mental adaptation, whereas infusions of synthetic oxytocin increased prolactin and mental adaptation. Oxytocin infusion also restored negative effects induced by caesarean section and epidural analgesia. Conclusions Oxytocin is released in response to breastfeeding to cause milk ejection, and to induce physiological changes to promote milk production and psychological adaptations to facilitate motherhood. Stress and medical interventions during birth may influence these effects and thereby adversely affect the initiation of breastfeeding.
Keywords: Corticotropin; Hydrocortisone; Oxytocin; Somatostatin; Prolactin; Breast feeding